Immigration and desire in the city of Washington Cucurto - de Aldama Ordónez, Celia (Romanica Olomucensia, 2019)
Taking a panoramic perspective as a starting point, the analysis proposed here of the short stories of the Argentine writer Washington Cucurto intends to relate them to the pornoerotic literature that has been booming in the cultural milieu of Buenos Aires in recent decades. First, the author will be contextualized as an heir of such literary aesthetics and second, a brief overview of the changes that have occurred in the literary representation of eroticism from the '80s to the first years of the 21st century will be provided. The second part of the research will focus on the analysis of three of his most read stories - "El barrio de las siervas", "El Rey de la Cumbia contra los fucking Estados Unidos de América", and "Paraguayito de mi corazón" - with the purpose of observing the dialogue that occurs in them between the literary approach to the theme of sex and its political significance. From the patterns that build the pornoerotic scenes in these stories, an answer to the following questions will be proposed: What political referentiality underlies the texts under analysis? What relationship could be established in them between the representation of the body and its social environment? What do the stories of Cucurto denounce? The main result will be the observation that deviant and excessive forms of sexuality represent the most visible symptoms of the degradation of the politico-social body.
Keywords: Washington Cucurto; Buenos Aires; body; erotism; city